Feasibility study of white shrimp, Litopenaeus vannamei, culture in earthen ponds using brackish water of the Caspian Sea - S.M.V. Farabi email ; A.A. Salehi; R. Pourgholam; M. Ghanei Tehrani (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2016)
Litopenaeus vannamei (Boone, 1931) post-larvae 12 were obtained from Bushehr province and reared at the Caspian Sea Ecological Research Iinstitute (Mazandaran, Iran) in summer 2012 using brackish water of the Caspian Sea. Prior to start of the experiment, post-larvae were gradually adapted to brackish water. The shrimp was stocked in a 1000 m2 earthen pond with a stocking density of 31 individual/m2. The earthen pond was in quarantine without discharge valve. During the rearing period, there was no water exchange. The shrimp was reared for 85 days. The average daily growth, final mean weight, feed conversion ratio and final yield were 0.31±0.04 g, 21.11±0.71 g, 0.79 and 531 kg, respectively. The results showed that L. vannamei can growth well in brackish water of Caspian Sea (salinity of 11.1±0.7 ppt and temperature of 28.67±0.72 °C) in Mazandaran province from July to September.